2017
DOI: 10.1016/j.jtcvs.2016.12.059
|View full text |Cite
|
Sign up to set email alerts
|

Aortic shear stress in patients with bicuspid aortic valve with stenosis and insufficiency

Abstract: Objectives Bicuspid aortic valve (BAV), characterized by valve malformation and risk for aortopathy, displays profound alteration in systolic aortic outflow and wall shear stress (WSS) distribution. The present study performed 4-dimenstional flow MRI in BAV patients with right-left (R-L) cusp fusion, focusing on the impact of valve function upon hemodynamic status within ascending aorta. Methods Four-dimensional flow MRI was performed in 50 R-L BAV subjects and 15 age- and aortic size-matched controls with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 47 publications
5
40
0
Order By: Relevance
“…The presence of aortic stenosis was associated with a further increase in WSS . Data regarding the particular effect of AR appear conflicting . Our findings of increased WSS in AR are in accord with the study by Shan et al that showed systolic WSS to be elevated in the AR subgroup of 15 BAV patients.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The presence of aortic stenosis was associated with a further increase in WSS . Data regarding the particular effect of AR appear conflicting . Our findings of increased WSS in AR are in accord with the study by Shan et al that showed systolic WSS to be elevated in the AR subgroup of 15 BAV patients.…”
Section: Discussionsupporting
confidence: 86%
“…Elevated WSS in BAV has been previously reported . The presence of aortic stenosis was associated with a further increase in WSS .…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations